Daughter of fortune : a novel - Allende, Isabel; Peden, Margaret Sayers (New York, NY : HarperCollins, 1999)
Eliza Sommers, left alone and pregnant in Chile when her lover Joaquin runs off to California during the Gold Rush, decides to follow him only to become entranced with her new life of freedom and independence.
Adult
Adult
Wilson's Senior High School
Wilson's Fiction
Library Journal
1250
Keywords: Chile -- Fiction; California -- Fiction; Love -- Fiction; Chile -- Fiction; California -- Fiction; Love stories; Historical fiction